2019
DOI: 10.1371/journal.pone.0214419
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine as an additive to improve the deposition of continuous electrospun filaments

Abstract: Electrospun filaments are leading to a new generation of medical yarns that have the ability to enhance tissue healing through their biophysical cues. We have recently developed a technology to fabricate continuous electrospun filaments by depositing the submicron fibres onto a thin wire. Here we investigate the influence of pyridine on the fibre deposition. We have added pyridine to polydioxanone solutions at concentrations ranging from 0 to 100 ppm, increasing the conductivity of the solutions almost linearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
11
0
1
Order By: Relevance
“…Electrospun monofilaments of PDO were produced according to previously described methods 40 . Polydioxanone (PDO; Riverpoint Medical, Portland, USA) was dissolved in 1,1,1,3,3,3‐hexafluoroisopropanol (HFIP; Halocarbon Product Corporation, Atlanta, USA) at a concentration of 7% (w/v) in the presence of pyridine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospun monofilaments of PDO were produced according to previously described methods 40 . Polydioxanone (PDO; Riverpoint Medical, Portland, USA) was dissolved in 1,1,1,3,3,3‐hexafluoroisopropanol (HFIP; Halocarbon Product Corporation, Atlanta, USA) at a concentration of 7% (w/v) in the presence of pyridine.…”
Section: Methodsmentioning
confidence: 99%
“…Electrospun monofilaments of PDO were produced according to previously described methods. 40 Polydioxanone (PDO; Riverpoint Medical, Portland, USA) was dissolved in 1,1,1,3,3,3-hexafluoroisopropanol (HFIP; Halocarbon Product Corporation, Atlanta, USA) at a concentration of 7% (w/v) in the presence of pyridine. Electrospinning was performed in a glove box using a single-nozzle highvoltage power supply system (30 kV, SL30P30/230; Spellman, West Sussex, UK) and a syringe pump (World Precision Instruments Limited, Florida, USA).…”
Section: Manufacture Of Electrospun Suturesmentioning
confidence: 99%
“…Nevertheless, the dynamic viscosity ( η ’) of PLGA is higher than PCLGA, although there is no statistical significance. However, it has been reported that the addition of pyridine decreases the dynamic viscosity [ 22 ]. Moreover, a higher dynamic viscosity entails a more uniform distribution of the nanofibers, as can be observed in Table 2 for PLGA.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of using pyridine in electrospinning is that it is not necessary to remove it after the process because it evaporates during the solution fly between the needle and the collector [ 20 , 21 ]. Moreover, it is an FDA-approved compound and has already been used as an additive in the pharmaceutical, agricultural or food industries [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrospinning solutions were prepared by dissolving variable quantities of PDO resin (Riverpoint Medical, Portland, United States) in Hexafluoro-2-propanol (Apollo Scientific Ltd, Cheshire, United Kingdom), with or without the addition of pyridine (purity >99.5%, PhEur grade, EMSURE ACS, Merck, Darmstadt, Germany) ( Lach et al, 2019 ), to obtain the required mass concentration (% w/v) of PDO solution ( Supplementary Tables S1, S2 ). The solution was agitated at room temperature on a roller set on speed of 15 RPM for at least 24 h to allow for complete dissolution of the polymer.…”
Section: Methodsmentioning
confidence: 99%